2019
DOI: 10.3389/fncir.2019.00063
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Physiology of Neurons in Layer 9 of the Chicken Optic Tectum

Abstract: Visual information in birds is to great extent processed in the optic tectum (TeO), a prominent laminated midbrain structure. Retinal input enters the TeO in its superficial layers, while output is limited to intermediate and deeper layers. In addition to visual information, the TeO receives multimodal input from the auditory and somatosensory pathway. The TeO gives rise to a major ascending tectofugal projection where neurons of tectal layer 13 project to the thalamic nucleus rotundus, which then projects to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Methods of isolating primary neurons from mice have been well studied in the past ( Chen et al, 2011 ; Jones et al, 2012 ). Due to the essential differences in brain tissue structure between birds and mammals ( Kloos et al, 2019 ; Stacho et al, 2020 ), their primary neuron culture methods may also differ significantly. Culturing avian primary neurons in vitro can better reflect the dynamic order of avian brains infected with viruses, so it is required that avian primary neurons are used as infection models to further study the relevant pathogenic mechanisms of avian neurological diseases such as Newcastle Disease Virus ( Wang et al, 2019 ), Marek's disease virus ( Gimeno et al, 2001 ), Tembusu virus ( Sun et al, 2014 ), and Japanese Encephalitis Virus ( Di et al, 2020 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Methods of isolating primary neurons from mice have been well studied in the past ( Chen et al, 2011 ; Jones et al, 2012 ). Due to the essential differences in brain tissue structure between birds and mammals ( Kloos et al, 2019 ; Stacho et al, 2020 ), their primary neuron culture methods may also differ significantly. Culturing avian primary neurons in vitro can better reflect the dynamic order of avian brains infected with viruses, so it is required that avian primary neurons are used as infection models to further study the relevant pathogenic mechanisms of avian neurological diseases such as Newcastle Disease Virus ( Wang et al, 2019 ), Marek's disease virus ( Gimeno et al, 2001 ), Tembusu virus ( Sun et al, 2014 ), and Japanese Encephalitis Virus ( Di et al, 2020 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that 5-HTR1F was expressed in layers 5a and 9 of the chick OT ( Figures 4B,B′ ). Recently, a detailed morphological and physiological study of neurons in layer 9 of chicken OT demonstrated the nature of input received in retinal projection via glutamatergic synapses ( Kloos et al, 2019 ). Taken together, it might be possible that 5-HTR1F -expressing neurons in the IHA and layers 5a and 9 in the OT share a common function in processing sensory input under serotonergic modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Given that sex differences in animals are rarely considered in researches that are conducted at the level of subcortical neurons (Ahmadlou et al 2018;Garrido-Charad et al 2018;Wohlgemuth et al 2018;Kloos et al 2019;Deichler et al 2020;Schryver et al 2020;Mahajan & Mysore 2022;Weigel et al 2022) and that most of the relevant papers on SSA do not pay attention to animal sex (Netser et al 2011;Dutta et al 2016;Wasmuht et al 2017;Valdés-Baizabal et al 2020;Lee et al 2020b;Jia et al 2021;Feng et al 2022), the neuronal recordings in this study were conducted in male and female pigeons (Columba livia, 350-450-g body weight). The pigeons were housed in individual wire mesh cages under a 12:12-h light-dark cycle with free access to water and food.…”
Section: Animal Preparationmentioning
confidence: 99%